PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Mauli, Afiyanisa; Mukaram, Mukaram (POLITEKNIK NEGERI BANDUNG, 2016)
CV Cihanjuang Inti Teknik is a company that produces micro hydro and turbine, as well as body warmers drinks in the food and beverage division (makmin). The company has 135 employees. Employee satisfaction is one of the important things that must be considered by a company because as this will impact on the performance of employees. Employees who are satisfied will have the awareness to do the more responsible duties at the company. But the reality on the ground there are some employees who are often absent from work, it is seen through the attendance percentage of employees who are still far from the target of work presence that is equal to 95%, while the rate of attendance of employees in 2015 was only 84.25%. There are also as many as 40% of employees feel less satisfied with promotion opportunities provided by the company. This resulted in employees feel lazy to work because they feel his efforts are not appreciated despite working diligently but can not get the appropriate results in the form of promotion (promotion). This study aims to determine job satisfaction and employee performance as well as the effect of job satisfaction on employee performance in CV Cihanjuang Inti Teknik. The method used is quantitative research methods. Data analysis methods used are descriptive statistical analysis, the classical assumption test, simple correlation analysis, linear regression analysis, and hypothesis testing. The sample in this study were 101 respondents. In the data collection used questionnaire with Likert scale. Based on the results of data processing, employee job satisfaction in the category both in terms of Work Itself, benefits, promotion opportunities, supervision, and Coworkers. Then the employee's performance was in the category good views of the Working Quantity, Quality of Work, Knowledge About Work, Personal Quality, Cooperation, Trustworthy, and Initiative. The conclusion of this research that there is an influence of job satisfaction on the performance of employees is 49,9%.